الأوضاع العامة بمنطقة وادي ريغ من خلال جريدة النجاح - الامام, بثينة; بن ويس, مختارية (جامعة الوادي - University of Eloued, 2023)
تميزت الأوضاع العامة في وادي 1925-1950 بالتدهور و الانحطاط ،فالجانب الاجتماعي منها عرف الفقر و الجوع مما دفع ببعض الأهالي إلى هجرت أراضيهم مثل قبيلة بن راشد ،و موالات بعض أعيان و مشايخ المنطقة لفرنسا خدمة لسياستها (باشا أغوات)، أما على الجانب الاقتصادي فقد سيطرت الشركات الاحتكارية عليها باعتبار تقرت مركز تجاري هاما ، و فيما يخص الجانب السياسي تبين أن المنطقة عرفت إنتشار واسع لحركة أحباب البيان و الحرية سنة 1945 و أما الجانب الثقافي فأخذ يقاوم السياسة الاستعمارية هذا ما رصدته جريدة النجاح. The general economic social and political conditions in were marked by decline and deterioration. The social conditions collared due to hunger and poverty, which prompted people and has taken control co lineal firms on the trade inTouggourt, which was an important commercial and economic center. As for the political situation, it seems that the did not know the spread of political parties in it until after the arrival of the <lovers of the statement and freedom>movement to it in 1945.<An Najah>newspaper monitored to migrate from the r areas like<The tibe of Ibn Rashid> due to the luck of water ,and the loyalties of the notables <Bache wates and Aghawates> in the service of authorities ,some ofthese conditions in .
مذكرة ماستر تاريخ معاصر